ChemInform Abstract: Ionothermal Synthesis, Crystal Structure, and Magnetic Study of Co2PO4OH Isostructural with Caminite. Issue 21 (27th May 2014) - Wang, Guangmei; Valldor, Martin; Spielberg, Eike T.; Mudring, Anja‐Verena
Abstract The title compound is prepared by reaction of Co(O‐Ac)2 and 85% H3PO4 in the ionic liquid 1‐butyl‐4‐methyl‐pyridinium hexafluorophosphate (autoclave, 200 °C, 7 d).